2017
DOI: 10.1001/jamasurg.2016.5059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Background Liver Cirrhosis on Outcomes of Hepatectomy for Hepatocellular Carcinoma

Abstract: Comparison of the patterns and annual incidence of recurrence of HCC demonstrated that the poorer prognosis in the LC group was likely owing to a higher hepatocarcinogenic potential among patients with cirrhosis. Annual recurrence rates in the 2 groups indicate that de novo recurrence may continuously occur from the early postoperative period until the late period after resection of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 33 publications
8
73
3
Order By: Relevance
“…However, the operation time was longer in the narrow RM group than in the wide RM group because parenchymal transection is more difficult in cirrhotic liver, and postoperative bile leakage was more frequent in the narrow RM group. As previously reported, the patients with cirrhotic liver experienced postoperative de novo recurrence because of higher carcinogenic potential [36, 37]. In this study, cirrhotic liver was related with disease recurrence with marginal significance in all patients.…”
Section: Discussionsupporting
confidence: 63%
“…However, the operation time was longer in the narrow RM group than in the wide RM group because parenchymal transection is more difficult in cirrhotic liver, and postoperative bile leakage was more frequent in the narrow RM group. As previously reported, the patients with cirrhotic liver experienced postoperative de novo recurrence because of higher carcinogenic potential [36, 37]. In this study, cirrhotic liver was related with disease recurrence with marginal significance in all patients.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, despite intending to include Child-Pugh A and early B patients in the study (as indicated in the methods section), the final data includes only patients with class A. Lastly, in this study, around 25% of patients, though suspected to have cirrhosis, did not meet histologic criteria on final pathological examination. This finding could potentially affect the results of the study, as recent data suggest that cirrhosis was associated with poorer prognosis, in part due to higher hepatocarcinogenic potential among these patients (4). Taken together, findings from this work confirm prior data demonstrating the safety of laparoscopy in patients with Child-Pugh class A associated HCC.…”
Section: Editorialsupporting
confidence: 83%
“…For patients with HCC receiving curative resection, ETR usually leads to poor prognosis . Various clinicopathological risk factors, especially portal vascular invasion, have been demonstrated to be significantly correlated with ETR . In this study, GAM analysis enabled us to reveal that tumour size, serum AFP level and the mRNA expression levels of KLB , FGF19 and CCND1 were significantly associated with ETR.…”
Section: Discussionmentioning
confidence: 84%